Limits on the Electromagnetic Counterpart of Binary Black Hole Coalescence at Visible Wavelengths - Kanthanakorn Noysena (2020)
© 2019. The American Astronomical Society. All rights reserved.. We used the Télescope Action Rapide pour les Objets Transitoires network of telescopes to search for the electromagnetic counterparts of GW150914, GW170104, and GW170814, which were reported to originate from binary black hole merger events by the Laser Interferometer Gravitational-wave Observatory and Virgo collaborations. Our goal is to constrain the emission from a binary black hole coalescence at visible wavelengths. We developed a simple and effective algorithm to detect new sources by matching the image data with the Gaia catalog Data Release 1. Machine learning was used and an algorithm was designed to locate unknown sources in a large field of view image. The angular distance between objects in the image and in the catalog was used to find new sources; we then process the candidates to validate them as possible new unknown celestial objects. Though several possible candidates were detected in the three gravitational-wave source error boxes studied, none of them were confirmed as a viable counterpart. The algorithm was effective for the identification of unknown candidates in a very large field and provided candidates for GW150914, GW170104, and GW170814. The entire 90% GW170814 error box was surveyed extensively within 0.6 days after the gravitational-wave emission resulting in an absolute limiting R magnitude of -23.8. This strong limit excludes to a great extent a possible emission of a gamma-ray burst with an optical counterpart associated with GW170814.